2001
DOI: 10.1016/s0377-0427(00)00678-6
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics of orthogonal polynomials inside the unit circle and Szegő–Padé approximants

Abstract: We study the asymptotic behaviour of orthogonal polynomials inside the unit circle for a subclass of measures that satisfy Szegő's condition. We give a connection between such behavior and a Montessus de Ballore type theorem for Szegő-Padé rational approximants of the corresponding Szegő function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 7 publications
3
36
0
Order By: Relevance
“…Theorem 2.8 is due to Barrios-L6pez-Saff [31] who also treat cases where, for Ibl < I, anb-n approaches a periodic sequence.…”
Section: ~mentioning
confidence: 99%
“…Theorem 2.8 is due to Barrios-L6pez-Saff [31] who also treat cases where, for Ibl < I, anb-n approaches a periodic sequence.…”
Section: ~mentioning
confidence: 99%
“…for some p, then α n+1 /α n is periodic of period p, and this overlaps examples of BLS [1] discussed later.…”
Section: Figurementioning
confidence: 62%
“…Section 5 will use the ideas in [7]. Finally, Section 6 makes various remarks about the connection to [1]. Figures 1 and 2 suggest that there might be a connection between the gaps in the clock and the Nevai-Totik zeros since in these two cases the number of NT zeros equals the number of gaps, and the zeros are near the gaps.…”
Section: Figurementioning
confidence: 99%
“…Simon [18] proved that r(z) -S(z) is analytic in {z I 1 -E < Izi < R2} when (3.1) holds, thereby generalizing [1]. The ultimate result of this genre was found independently by Deift-Ostensson [7] and Martinez-Finkelshtein et al [13]; an alternate proof was then found by Simon [20].…”
Section: Theorem 32 ([6]mentioning
confidence: 97%
“…To understand the situation when J has bound states, we note the analytic continuation of (1.16) says Barrios Rolania et al [1] …”
Section: Theorem 32 ([6]mentioning
confidence: 99%